No augmentation of indoleamine 2, 3-dioxygenase (IDO) activity through belatacept treatment in liver transplant recipients. (2nd February 2018) - Bigenzahn, S; Juergens, B; Mahr, B; Pratschke, J; Koenigsrainer, A; Becker, T; Fuchs, D; Brandacher, G; Kainz, A; Muehlbacher, F; Wekerle, T
Summary: Belatacept is a second-generation cytotoxic T lymphocyte antigen (CTLA)-4 immunoglobulin (Ig) fusion protein approved for immunosuppression in renal transplant recipients. It was designed intentionally to interrupt co-stimulation via CD28 by binding to its ligands B7·1 and B7·2. Experimental evidence suggests a potential additional mechanism for CTLA-4 Ig compounds through binding to B7 molecules expressed on antigen-presenting cells (APCs) and up-regulation of indoleamine 2, 3-dioxygenase (IDO), an immunomodulating enzyme that catalyzes the degradation of tryptophan to kynurenine and that down-regulates T cell immunity. So far it remains unknown whether belatacept up-regulates IDO in transplant recipients. We therefore investigated whether belatacept therapy enhances IDO activity in liver transplant recipients enrolled in a multi-centre, investigator-initiated substudy of the Phase II trial of belatacept in liver transplantation (IM103-045). Tryptophan and kynurenine serum levels were measured during the first 6 weeks post-transplant in liver transplant patients randomized to receive either belatacept or tacrolimus-based immunosuppression. There was no significant difference in IDO activity, as indicated by the kynurenine/tryptophan ratio, between belatacept and tacrolimus-treated patients in per-protocol and in intent-to-treat analyses. Moreover, no evidence was found that belatacept affects IDO in human dendritic cells (DC) in vitro . These data provide evidence that belatacept is not associated with detectable IDO induction in the clinical transplant setting compared to tacrolimus-treated patients. Graphical Abstract: